PENYEDIAAN ENERGI LISTRIK BERBASIS PERBEDAAN SALINITAS DENGAN MENGGUNAKAN TEKNOLOGI REVERSE ELECTRODIALYSIS - Yoga Prasetya; Meindy Catur Risqiputra; Heru Susanto (Jurusan Teknik Kimia, Fakultas Teknik, Universitas Diponegoro,, 2013)
Since the formation of the Kyoto's Protocol and is based on reports of the Intergovernmental Panel on Climate Change (IPCC) about the capture and storage of carbon dioxide gas in order to reduce the rate of climate change, there is a continual effort that oriented to the handling of CO2 emissions into the atmosphere, Although Indonesia has never been obligated to reduce its emissions, but this policy will have a big impact on Indonesia, especially in the energy sector. Until now, oil is still the main source of energy in fulfilling energy needs within the country. The role of a very large petroleum will continue, while the dwindling petroleum reserves.Recognizing the dependence on fossil fuels, there should be an effort to press the growth of the use of fuel oil . Nowadays, it has developed an alternative energy known as the Salinity Gradient Energy (SGE). Sanility Gradient Energy has great potential for use as an alternative energy especially in Indonesia, which is the state waters. This research is aimed for study the effect of the concentration of concentrated NaCl solution, dilute NaCl solution flow rate, feed of seawater synthesis and real sea water in generated of power density. This research started inmaking a concentrated NaCl solution with various concentrations of as much as 2 l and a dilute NaCl solution with a concentration of 1 g/l as much as 2 l. Continued with the second turning on the pump diaphragm for both types of feed solution flow into the channels contained in a series of tools. After a few moments appliance operates, the change of output voltage (V) and electric current (A) can be measured using a multitester, this measurement conducted every 20 seconds interval. and then repeat the same steps for each of the variables that have been defined.From this research was found that increase in feed flow rate, then the resulting power density is greater, because of the increased flow rate causes the rate of movement of ions to the electrode increases. on increasing of the concentrated NaCl solution, the resulting power density is greater, because of the increased concentration difference causes an increase in the chemical potential. And for sample nearly the same concentration (30 g/l), the resulting power density of sea water is greater than the synthesis of real sea water, because the value of electrolytes activation synthesis of sea water is greater than the real sea water. It can be concluded that the increase in flow rate and concentration, can increase the generated of power density.